History of mathematics education, objectified knowledge and the constitution of a discipline - Oliveira, Maria Cristina Araújo de (Historia y Memoria de la Educación, 2019)
The purpose of this paper is to discuss the role of the History of mathematics education (HEM) in the training of teachers who teach mathematics. We propose the insertion of this specialized knowledge as a subject in undergraduate and postgraduate courses. In this sense we intend to show the relevance of the exploration, at the teaching level, of the knowledge previously produced in the field of research in the history of mathematics education for the training of teachers in this subject. In general, it can be said that research in this field is guided by issues close to the professional practices of teachers, which can be denatured if examined from a historical point of view. By giving the results of studies produced on HEM the form of a discipline accessible to the teachers in training, we believe we can create the possibility of linking teaching with research in a way that ensures a differentiated contribution to school mathematics and fosters new research questions.